2019
DOI: 10.1111/aas.13375
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for ICU admission may increase the risk of death—A plea for better resource organization

Abstract: Overall hospital mortality of critically ill patients has been reported to range from 13.5% to 31%, and it has been the subject of extensive research in order to understand which patients are at a higher risk of dying. 1,2 The survival curve related to Intensive Care Unit (ICU) admission is known to be determined in the short term by characteristics of the acute illness and the related residual organ dysfunction and by individual characteristics, like age and comorbidities in the long term. 3,4 Multiple other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…While some studies have demonstrated an association between mortality and delays in ICU admission, [ 24 , 25 ] others have reported contradictory results. For example, a prospective cohort study of 1675 patients admitted to the ICU showed that the length of ED stay was not associated with hospital mortality ( P = 0.82) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have demonstrated an association between mortality and delays in ICU admission, [ 24 , 25 ] others have reported contradictory results. For example, a prospective cohort study of 1675 patients admitted to the ICU showed that the length of ED stay was not associated with hospital mortality ( P = 0.82) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even if intubation is deemed necessary and timely accomplished, a prolonged stay in the ED with delayed ICU admission is another issue. Undeniably, delayed ICU admission has shown a significant impact on critically ill patients [15] , [16] , and there are no reasons why this should impact differently in specific disease as COVID-19. Certainly, a mechanically ventilated patient remaining for several hours in the ED because of absence of ICU beds will not receive the specialized treatment that can be fully delivered only in the ICU.…”
mentioning
confidence: 99%